1996
DOI: 10.1093/jn/126.2.516
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and Liver Protein Synthesis Adapt Efficiently to Food Deprivation and Refeeding in 12-Month-Old Rats

Abstract: Our aim was to analyze mechanisms involved in the adaptation of protein metabolism to food deprivation and refeeding in adult rats. Twelve-month-old rats, which had been food-deprived for 113 h and refed for 6 h, were injected subcutaneously with a flooding dose of valine (with 50% [1-13C]-L-valine) to measure in vivo protein synthesis in tibialis anterior, soleus and liver. Protein and RNA contents were also measured. In both muscles, protein mass was maintained during food deprivation. Due to a drop in prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 24 publications
5
26
1
Order By: Relevance
“…There was a Ͻ10% difference between free valine enrichments in plasma, gastrocnemius, and liver (88-89%, 84-87%, and 78-85% of injected valine, respectively). We also demonstrated that free valine enrichment in plasma reached 89% of the plateau value within 5 min after injection and remained stable for more than 45 min (23). These measurements were made between 1:30 PM and 4:30 PM in fed or refed rats (postprandial state) and between 9 AM and 11 AM in starved rats.…”
Section: Methodssupporting
confidence: 51%
See 3 more Smart Citations
“…There was a Ͻ10% difference between free valine enrichments in plasma, gastrocnemius, and liver (88-89%, 84-87%, and 78-85% of injected valine, respectively). We also demonstrated that free valine enrichment in plasma reached 89% of the plateau value within 5 min after injection and remained stable for more than 45 min (23). These measurements were made between 1:30 PM and 4:30 PM in fed or refed rats (postprandial state) and between 9 AM and 11 AM in starved rats.…”
Section: Methodssupporting
confidence: 51%
“…We used male Sprague-Dawley rats (obtained from Iffa Credo, Lyon, France) aged 12 or 24 mo at the end of the experimentation. They were maintained in individual metabolism cages at 22°C with a 12:12-h lightdark cycle (lights on from 9 PM to 9 AM) with free access to water; they were weighed daily and were offered a semiliquid casein-based diet containing 18.7 g protein/100 g dry matter, as described previously (23). The animals had free access to food between 9 AM and 5 PM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, feeding has little effect on muscle protein synthesis in adult mammals (Melville et al 1989;Baillie and Garlick, 1992;Tessari et al 1996). By contrast, feeding stimulates liver protein synthesis in both growing (Burrin et al 1992 and adult (Preedy et al 1988;Mosoni et al 1996) animals.…”
Section: Protein Deposition Is Developmentallymentioning
confidence: 92%